Sources about the Voloshyn Regime's Concentration Camp at Dumen Hill in 1938–1939 - B. Stenge Csaba (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. This paper is a study and few primary sources about the concentration camp near Rakhiv at Dumen hill, run by the Voloshyn-regime. Beyond the general information and summary, it contains several original documents, primary sources from the middle of December, 1938 written by the Czechoslovak gendarmerie about the camp.

Ez a tanulmány és forrásközlés a Volosinrezsim által a Rahó melletti Dömény-havason felállított koncentrációs táborral foglalkozik. Az általános ismertetőn és összefoglalón túl leközlésre kerül néhány 1938 decemberének közepén keletkezett csehszlovák csendőrségi dokumentum, melyek ritka, fennmaradt elsődleges források a koncentrációs táborral kapcsolatban.

Резюме. У публікації розглянуто джерела, присвячені концентраційному табору «Думен», зведеному режимом А.Волошина поблизу Рахова. Крім загальних відомостей, детальніше презентовано кілька документів чехословацької жандармерії, датованих серединою грудня 1938 року. Це рідкісні автентичні джерела, що містять відомості про концентраційний табір.
Források a Volosin-rezsim 1938–1939-ben működő Dumenhegyi koncentrációs táboráról
Джерела про концентраційний табір «Думен», що функціонував за режиму А. Волошина в 1938-1939 роках
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008907
Keywords: Carpathian Ruthenia; Voloshyn; Carpathian Sich; Dumen hill; concentration camp; internment